Integrasi teknologi dalam pembelajaran: Upaya untuk beradaptasi dengan tantangan era digital dan revolusi industri 4.0 - Afrianto Daud; Ando Fahda Aulia; Nita Ramayanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
The era of the Industrial Revolution 4.0 has brought new challenges and opportunities to education. One of them is the increasing opportunities for teachers to integrate technology into the learning process so that learning outcomes can be more effective. The problem is that not many teachers have the ability to integrate technology into their classrooms. This is especially the case for private school teachers with limited facilities. This Community Service Program seeks to help teachers equipped with this ability by introducing the use of Google Apps for Education, such as Google Classroom and Google Hangout for Learning. In addition, teachers are also trained with the video editing skills that they can use to make video-based learning media. The activity was carried out in the form of a workshop for teachers at Sekolah Juara Pekanbaru. This is a free school under the management of Indonesian Zakat Institution. The majority of students are coming from poor families. After the workshop, the teachers were also guided in the implementation/practice in the classroom. The program runs quite effectively. This can be seen from the comparison of the pre-test and the post-test given to the trainees. Four people (36.4%) from 11 participants stated that they had the ability to use the Google Classroom at a very good level, and five people (45.4%) were at a good level. This number is far different from the results of the pre-tests which showed that 10 (90.0%) of the 11 participants stated that they were not familiar with and were unable to use the Google Classroom application.